2020
DOI: 10.1088/1752-7163/abaeca
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS-based untargeted metabolomics of plasma and urine to evaluate metabolic changes in prostate cancer

Abstract: Prostate cancer (CaP) is a common cancer in men. Its late detection and inefficient diagnosis are a challenge for researchers who are currently searching for new cancer-related indicators that would facilitate better detectability of CaP and explain its pathogenesis. In the present preliminary study, endogenous volatile metabolites were detected in plasma and urine samples by using the metabolic fingerprinting approach. The analyses were performed using the GC-QqQ/MS technique in the scan mode. The detected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…However, the specific molecules responsible for this behavior remain unidentified. Previous studies have shown varying levels of certain molecules in cancerous urine compared to healthy controls [99][100][101][102][103]. For instance, in ovarian cancer, metabolites such as serine, glutamate, tyrosine, arachidonic acid, succinic acid, and acrylic acid are upregulated, while 2-phosphoenolpyruvate, benzoic acid, phenylacetic acid, nervonic acid, stearic acid, and creatinine are downregulated [104,105].…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific molecules responsible for this behavior remain unidentified. Previous studies have shown varying levels of certain molecules in cancerous urine compared to healthy controls [99][100][101][102][103]. For instance, in ovarian cancer, metabolites such as serine, glutamate, tyrosine, arachidonic acid, succinic acid, and acrylic acid are upregulated, while 2-phosphoenolpyruvate, benzoic acid, phenylacetic acid, nervonic acid, stearic acid, and creatinine are downregulated [104,105].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, 3-Hydroxyisobutyric acid and L-cystathionine were found to be more expressed in metastatic patients at diagnosis when compared to those after induction chemotherapy. 3-Hydroxyisobutyric acid is an intermediate in the metabolism of valine that has been found in elevated amounts in the urine of patients with various tumors (49,50). Cystathionine is an intermediate in the synthesis of cysteine produced by the trans-sulfuration pathway which converts homocysteine into cystathionine (51).…”
Section: Discussionmentioning
confidence: 99%
“…Untargeted metabolomic profiling has become a valuable tool for the identification of potential metabolic biomarkers in cancer (Struck-Lewicka et al, 2020;Kowalczyk et al, 2021) or the assessment of the response to anti-tumor therapy (Han et al, 2021;Ruan et al, 2022). In order to investigate dynamic pathway alterations in metabolic networks, untargeted stable isotope resolved metabolomics (SIRM) can be applied as a complementary tool (Huang et al, 2014) to evaluate the cellular fate of precursor metabolites and thereby enabling deeper insight into dysregulation of cancer metabolism and individual drug response phenotypes.…”
Section: Discussionmentioning
confidence: 99%